Le maître incertain : remarques sur la figure poppérienne de l'enseignant - Alain Firode (Nantes Université, 2018)
According to Karl Popper, a good teacher doesn't aim at winning his pupils' confidence. On the contrary, like the Greek philosopher and physicist Thales, he strives to challenge them to object to his own theories. This original way of conceiving the educational relationship, which consists of considering pupils as potential opponents, ensues from the essential principles of the popperian philosophy (i. e. "critical rationalism"). As a result, this leads to an anti-authoritarian conception of education that focuses on the development of critical thinking.